Pengaruh Gaya Kepemimpinan Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Anugerah Autocentra Abadi Jakarta - Ali Andu Prasasti; Henni Marlinah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This study aims to determine the effect of leadership style and compensation on employee performance at PT. Anugerah Autocentra Abadi Jakarta. The background of this study is the importance of the role of leaders in directing and motivating employees, and providing appropriate compensation to improve performance. The method used is descriptive quantitative with saturated sample technique, involving 60 respondents. Data analysis includes validity, reliability, classical assumptions, simple and multiple linear regression, correlation coefficient, determination, and hypothesis testing. The results show that leadership style has a positive and significant effect on employee performance with a determination coefficient of 67.1% and t count > t table (10.876 > 2.001). Compensation also has a positive and significant effect on employee performance with a determination coefficient of 44.2% and t count > t table (6.772 > 2.001). Simultaneously, leadership style and compensation have a significant effect on employee performance with a determination coefficient of 68.4%, while the remaining 31.6% is influenced by other factors outside this study. This finding confirms that the application of appropriate leadership style and the provision of fair compensation can improve employee performance optimally. Keywords: Leadership Style, Compensation, Employee Performance.